Pengaruh Metode Demonstrasi terhadap Keaktifan Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VII SMP Negeri 4 Tarutung Tahun Ajaran 2023/2024 - Cindy Sriwahyuni Sihombing; Maria Wisdiatuti; Rusmauli Simbolon; Johari Manik; Goklas Manalu (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The aim of this research is to determine the positive and significant influence of the demonstration method on students' active learning in the Christian Religious Education and Character Education subjects in class VII SMP Negeri 4 Tarutung for the 2023/2024 academic year. The method used in this research uses a quantitative approach with inferential statistical analysis techniques. The population is all class VII students at SMP Negeri 4 Tarutung for the 2023/2024 academic year who are Protestant Christians, totaling 123 people and a sample of 37 people was determined, namely 30% of the population using the Simple Random Sampling technique. Data was collected using a positive closed questionnaire with 31 items. The results of data analysis show that there is a positive and significant influence of the demonstration method on students' active learning in the Christian Religious Education and Character Education subjects in class VII SMP Negeri 4 Tarutung for the 2023/2024 academic year: 1) Test the analysis requirements: a) test a positive relationship obtained rxy value = 0.503 > rtable(a=0.05,n=37) = 0.325, thus it is known that there is a positive relationship between variable 0.05,dk=n-2=35)= 2.042, thus there is a significant relationship between variable "+0.46X. b) Regression coefficient of determination test (r2) = 25.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=13, dk denominator=n-2=37-2=35) namely 11.84 > 2.09. Thus, Ha, that is, there is a positive and significant influence of the demonstration method on students' active learning in the Christian Religious Education and Character Education subjects for class VII SMP Negeri 4 Tarutung for the 2023/2024 academic year is accepted and H0 is rejected.